Performance Reviewed From Leadership Style, Organizational Culture, Workload And Employee Competency Of Grogol Community Health Center, Sukoharjo Regency - Siti Nurjanah; Istiatin Istiatin; Sudarwati Sudarwati (Universitas Pahlawan Tuanku Tambusai, 2025)
Performance Reviewed From Leadership Style, Organizational Culture, Workload and Competence of Grogol Health Center Employees, Sukoharjo Regency. This study aims to determine and explain the influence of leadership style, organizational culture, workload and competence on the performance of Grogol Health Center employees, Sukoharjo Regency.. The population of this study isGrogol Health Center employees as many as 120 people and saturated samples. Data collection using questionnaires. Data analysis techniques usingMultiple Linear Analysis method. The research results show thatleadership style, organizational culture, workload and competence have a positive and significant influence oncontributed to Performance by 77% while the remaining 23% was explained by other variables not submitted in this study. Suggestions from this study, Grogol Health Center Employees, Sukoharjo Regency can improve organizational culture and competence as well as the importance of leadership style that pays attention to the appropriate workload so as to improve performance in the office.